From Autonomy Support and Grit to Satisfaction With Life Through Self-Determined Motivation and Group Cohesion in Higher Education - Lozano-Jiménez, José Eduardo; Huéscar, Elisa; Moreno-Murcia, Juan Antonio (Frontiers in Psychology, 2021)
Using the Self-Determination Theory as a framework, this study tests the predictive capacity of the teacher’s interpersonal style of autonomy support at a higher education institution, and the grit on the satisfaction of basic psychological needs, intrinsic motivation, group cohesion and life satisfaction in university students. A sample composed of 489 Colombian university students (381 women and 108 man), aged between 18 and 41 years (M = 21.93; DT = 3.58), was used; they filled in the questionnaires that measured the variables of interest. After the analysis of structural equations, the results showed that the perception of teaching style of autonomy support and the grit positively predicted the basic psychological needs and these predicted the intrinsic motivation, which in turn predicted group cohesion and satisfaction with life. The model describes the possible importance of promoting the teacher’s interpersonal style of autonomy support within the university setting in the search for satisfaction with life along with the active role of the student through the mediation of the satisfaction of basic psychological needs, increased quality motivation and high group cohesion.